Hermeneutika Nasr Hamid Abu Zayd Dalam Metode Perkembangan Tafsir Modern - Muhammad Saekul Mujahidin (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractAl-Qur'an as the main source of Islamic law, has always been a reference for various problems from time to time. Along with developments and the emergence of comlexity of social problems, the interpretation of the Koran needs to continue to develop in accordance with current conditions. Al-Qur'an interpretation must be able to answer social, economic, cultural, political, religious, and other problems. Nasr Hamid Abu Zayd is a Muslim thinker in the field of hermeneutics who tries to contextualize the Koran in modern times. This research is qualitative research in the form of library research, the sources are obtained through books, journals or writings related to research. The results of this study indicate that Abu Zayd is a Muslim thinker who tries to interpret the Koran in an